70‐1: A New Approach to High‐Resolution Light Field Display for Higher Realistic Expression - Kang, Hoon; Park, MyungSoo; Jang, JuHoon; Kim, DongYeon; Koo, GyoHyun; Jung, GyuSuk; Kim, HeeCheol; Kim, GiHong; Yang, JoonYoung; Yoon, SooYoung (SID International Symposium Digest of technical papers, 2024)
We have developed a 31.5” Light Field Display with 3D resolution enhanced threefold compared to conventional design. This offers an approach that enables the realization of more realistic 3D images.